Leadership Education at Pondok Modern Darussalam Gontor Putra Campus 1, Ponorogo - Nurul Salis Alamin; Syarifah; Defi Firmansyah; Riza Ashari; Neri Wijayanti (Institut Attanwir Bojonegoro, 2024)
Leadership is the process of leading a group towards its goals. Pondok Modern Darussalam Gontor, an Islamic boarding school educational institution, emphasizes social orientation and leadership in its students. Its motto is